1973
DOI: 10.1039/p29730000742
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of N-bromo-N-sodiobenzenesulphonamide (bromamine B) with p-nitrophenoxide ion

Abstract: Box Forest Hall No. 2, Newcastle upon Tyne NE12 9TS By using the interaction with p-nitrophenol as a mechanistic probe it has been established that solutions of Nbromo-N-sodiobenzenesulphonamide (bromamine B) in dilute alkali contain two reactive brominating species, the conjugate acid (PhS0,NHBr) and hypobromous acid; formation of the latter can be suppressed by the addition of the parent sulphonamide. These solutions are fully described by a system of four equilibria: three are proton transfer reactions, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(112 citation statements)
references
References 0 publications
5
102
2
Order By: Relevance
“…Further, Hardy and Jhonston [29] have made detailed calculations on the relative concentrations of the reactive species in alkaline bromamine-B solutions and reported that HOBr is also the predominant species in alkaline medium. Since N-haloamines have similar properties and hence one can expect similar equilibrium for alkaline CAT solutions also as shown below, …”
Section: Discussionmentioning
confidence: 99%
“…Further, Hardy and Jhonston [29] have made detailed calculations on the relative concentrations of the reactive species in alkaline bromamine-B solutions and reported that HOBr is also the predominant species in alkaline medium. Since N-haloamines have similar properties and hence one can expect similar equilibrium for alkaline CAT solutions also as shown below, …”
Section: Discussionmentioning
confidence: 99%
“…Since organic N-haloamines have analogous chemical properties, it is predicted that identical equilibria exist in aqueous acidic and basic solutions of these compounds [25][26]. Chloramine-B and bromamine-B act as oxidizing agents in acidic and alkaline media [27][28][29] with a two electron change per mole giving benzenesulfonamide (BSA) and NaCl or NaBr. The redox potential of CAT-PTS couple is pH dependent [25] and decreases with increase in pH of the medium (E redox 1.138 V, 1.778 V, 0.614 V and 0.5 V at pH 0.65, 7.0, 9.7 and 12, respectively).…”
Section: Reactive Species Of Sodium N-halo-benzenesulfonamidesmentioning
confidence: 99%
“…The redox potential of CAB/BSA is pH dependent and decreases with increases in pH of the medium. Chloramine-B behaves as a strong electrolyte [19] in aqueous solutions and depending upon the pH of the medium it furnishes following types of reactive species in solutions [19][20][21] (Scheme 2).…”
Section: Polymerization Studymentioning
confidence: 99%